Bone Loss Following Cementless Hemiarthroplasty for the Treatment of Femoral Neck Fracture - Murat, Mert (Indian J Orthop, 2020)
BACKGROUND: With the advances in medicine, an increasing number of the ageing population are a public health concern in terms of age-related complications. Among them, displaced neck fractures often require surgical intervention or arthroplasty to achieve the mobilization of the elderly and good life quality. The aim of the study is to monitor the changes in bone mineral density (BMD) around the femoral stem and the effects on functional outcomes in patients treated with cementless hemiarthroplasty following femoral neck fracture. MATERIALS AND METHODS: Seventy-one patients aged 70 years or older who were treated with cementless hemiarthroplasty for a displaced femoral neck fracture were prospectively followed for 2 years. The percent change in the periprosthetic BMD in each Gruen zone was compared to the baseline using dual-energy X-ray absorptiometry (DEXA). Demographic factors [age, body mass index (BMI), and sex] that could possibly influence BMD and the clinical outcome were evaluated. RESULTS: Fifty-one patients were available for the final follow-up. The mean age was 76.5 (range 70–89) years. The mean BMI was 28.9 (range 22.7–37.2). The mean Harris hip score at the final follow-up was 84.3 (range 72–93). There was a significant decrease in BMD in all Gruen zones (p < 0.001), except in zone 3 (R3, p = 0.547). The reduction in BMD was highest in the calcar and the greater trochanter region. The femur diaphysis was relatively spared, with zone 3 showing no significant bone mineral loss. The age and BMI of the patients were not correlated with the postoperative change in BMD in any of the Gruen zones. The degree of reduction in bone density was not correlated with the clinical outcome. CONCLUSIONS: Cementless hemiarthroplasty for the treatment of femoral neck fracture in elderly patients achieves a good clinical outcome despite significant bone loss around the femoral stem. The reduction in BMD is more pronounced in the metaphyseal region.